Steam-flaked corn diets containing combinations of wet corn gluten feed and alfalfa hay: effects on diet digestibility and ruminal characteristics - J.J. Sindt; Sean P. Montgomery; J.N. Pike; T.B. Farran; C.M. Coetzer; James J. Higgins; James S. Drouillard; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2002)
Twelve ruminally cannulated Jersey steers were used to measure digestibility and ruminal characteristics of steam-flaked corn based diets containing combinations of wet corn gluten feed (WCGF) and alfalfa hay (AH). Starch intake was lower (P<0.05), but neutral detergent fiber intake was higher (P<0.05) as AH and WCGF increased in the diet. Ruminal pH was increased by AH (linear, P<0.05) and tended (P<0.07) to increase with WCGF. Feeding higher levels of WCGF tended to increase passage rate (P=0.17) and decreased (P<0.05) total tract organic matter digestibility. Flaked corn diets containing at least 25% WCGF may contribute enough roughage to allow reduction of alfalfa hay levels.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Wet corn gluten feed; Steam-flaked corn; Digestibility